The influence of the sleep-wake cycle on primary monosymptomatic nocturnal enuresis: A non-randomized comparative study - Erdoğan, Fırat; Kadak, Muhammed Tayyip; Selvi, Yavuz; Kartal, Vural; Şenkal, Evrim; Ateş, Burçin; Akgül, Murat (Taylor and Francis Ltd., 2016)
Backround: Enuresis implies severe stress in affected children, and impairs quality of life and sleep. Children with enuresis experience difficulties in their arousal from sleep, possibly associated with disturbances of the circadian rhythm. In this study, we aimed to evaluate the sleep-wake cycle and sleep disturbances in children with monosymptomatic enuresis nocturna (MEN). Method: The study comprised 70 children with MEN who were admitted to the pediatrics and urology outpatients department and 94 age-matched healthy controls. Parents completed "Strengths and Difficulties Questionnaire," Children's Sleep Habits Questionnaire (CSHQ), Children's Chronotype Questionnaire scale. Results: Children with enuresis had significantly more sleep and psychological problem. Enuresis group reported higher bedtime resistance, parasomnias, breathing-related problems, and daytime sleepiness in CHSQ (p < 0.05). Although circadian preference did not differ statistically between the groups (p > 0.05), sleep duration on school days and awakening and mid-sleep points, both on scheduled and free days, were found to be significantly different in the enuretic group (p < 0.05). In logistic regression analysis, age, sleep period on scheduled days, sleep inertia on scheduled and free days were significant predictor for enuresis. Discussion: Children with enuresis were more likely to experience problematic sleep. This may reflect that enuretic children have impaired sleep-wake cycles, leading to dysregulation of daily functional changes of bladder capacity and related hormones such as ADH. These findings might imply a sleep-wake disturbance in enuresis.
Keywords: Biological Rhythm; Circadian Preferences; Enuresis; Sleep-Wake Cycle